NILAI EDUKASI KASIH SAYANG DALAM KEHIDUPAN RUMAH TANGGA RASULULLAH SAW - Hasanah Hasanah; Siti Salmi (Jurnal Dedikasi Pendidikan, 2017)
This study entitled "The Education Value of  Love in the Prophet Household Life". Love is a potential feeling that exists since a man was born but needs to be developed further in order to have a strong sense to love  the people around and his family, it also have to be developed and mentored in order to improve human character. However the households nowadays do not reflect the Prophet teachings. Even husband and wife who were married themselves do not understand the meaning of marriage itself, marriage is supposed to a husband and wife should love each other, educating their children, because education should be implemented first in the family. Wives nowadays much complain to the material things, that should not be done by a wife, otherwise they had to be grateful for every pleasure given by Allah, as exemplified by Khadija, who never complained even though she lived in a shortage life. Based on the problems above, the research questions of this thesis are: How the analysis pattern of education in the Prophet household?. How forms of affection in relationship educational value ?. How affectionate behavior in the household and educational value ?. How the application values of the Prophet household affection in contemporary education ?. The Method that used in  this research is a literature study (library research) using primary and secondary data sources, then the data were analyzed using descriptive method of analysis of the available data documentation. The results of the research in this study is the analysis patterns of education in the Prophet household which shows that education have to be applied first in the family, because family is the first foundation in forming children character.